Ukrainian Chekhovian of the end of the XIX – early XX centuries: Mikhail and Mariya Grushevsky - Борбунюк, Валентина Олексіївна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2018)
The article describes the works of Mariya and Mykhaylo Grushevsky, related to the work of A.Chekhov, translation and scientific and critical reflection of his works on the pages of "Literary and scientific journal". It was shown that translations of M. Grushevska were performed at a high professional level in line with the new requirements for the translation technology of the early twentieth century, which increased attention to the purity and correctness of the Ukrainian language. The Chekhov knowledge activity of Grushevsky testifies to the soundness of philological training, profound knowledge of the subject under discussion, tolerance and constructiveness of the assessments. The research clearly demonstrates that thanks to Mykhaylo and Mariya Grushevsky, the Ukrainian nation was "conquered" / mastered one of the most prominent human cultural achievements - the Chekhov phenomenon, the foundations of the development of Ukrainian Chechen studies, the prospects for further research. The Ukrainian Chekhov project, initiated by Mikhaylo and Mariya Grushevsky, was and remains not only a continuation of the dialogue between the two cultures, but also one of the unifying cultural cultivating factors of the Ukrainian nation.